Нелинейные нормальные формы вынужденных колебаний кусочно-линейных систем при супергармонических резонансах - Успенский, Б.В.; Аврамов, К.В.; Никонов, О.Я. (Проблемы машиностроения, 2017)
Предложен метод расчета вынужденных колебаний существенно нелинейных кусочно-линейных систем при супергармонических резонансах. В основе этого метода лежит сочетание нелинейных нормальных форм и метода Раушера, с помощью которого неавтономная динамическая система сводится к эквивалентной автономной. С помощью предложенного метода исследуются супергармонические колебания в участке силовой передачи двигателя внутреннего сгорания. Подробно рассматриваются свойства резонансных колебаний. Запропоновано метод розрахунку вимушених коливань суттєво нелінійних кусково-лінійних систем при супергармонійних резонансах. Метод базується на поєднанні нелінійних нормальних форм та методу Раушера, завдяки якому неавтономну динамічну систему зведено до еквівалентної автономної. За допомогою запропонованого методу досліджено супергармонійні коливання в ланці силової передачі двигуна внутрішнього згоряння. Детально розглянуто властивості резонансних коливань. The paper describes a new technique for analysis of forced oscillations in strongly nonlinear piecewise linear systems considering superharmonic resonances. Nonlinear oscillations of piecewise linear systems have complex behavior including bifurcations, chaotic oscillations, sub- and superharmonic responses. Extreme importance of piecewise linear systems analysis due to their abundance in machinery and, particularly, engines makes the problem of nonlinear oscillatory dynamics in such systems highly topical. Nonlinear normal modes as an approach for analysis of nonlinear oscillations were developed by Rosenberg. Shaw and Pierre amended this approach using an invariant manifolds ideology. This paper utilizes and modifies Shaw-Pierre nonlinear normal modes approach to analyze superharmonical oscillations occurring in piecewise linear mechanical systems under harmonic excitation. The Rauscher technique is used to bring a non-autonomous dynamical system to an equivalent pseudo-autonomous one. To commit analysis of superharmonic resonances in the system, a modification to the Rauscher method is proposed. Eventually, an analysis of a mechanical system modeling a circuit of a power transmission of an internal combustion engine is performed. Amplitude-frequency diagram is obtained for the second superharmonical resonance. It is discovered that in the configuration space the second superharmonical nonlinear normal mode contains delamination that prevents it to be found using Rosenberg nonlinear normal modes technique.